(untitled) (Al-Qamar, 2025)
Second language acquisition is a complex process that can be influenced by a variety of factors. The current paper aims to identify the potential factors affecting the teaching and learning of students. Adopting a case study approach, this study suggests that there may be four potential causal factors that undermine the quality of teaching/learning in the BISE. (1) over-crowded classrooms (2) course content (3) teachers’ professional development and (4) the examination system. To explore these issues, this study set two research questions. What are the causes of declining standards of teaching and learning English within the Board of Intermediate and Secondary Hyderabad? 2. How can a teacher change thinking and classroom practices to improve the Progress of learners in education? A constructivist grounded theory approach was adopted. This qualitative case study was conducted using carefully designed interviews and data was analyzed qualitatively. it was found that structural redefinition of the culture of teaching is inevitably required for teachers to lead educational change process within the BISE.